Estágio curricular e a constituição da identidade profissional do bacharel em educação física - Anversa, Ana Luiza Barbosa (2017)
Identity is related to the feeling of belonging and an element in continuous construction and reconstruction from the perceptions presented by individuals about themselves, others and established socializations. In a professional context, identity relates to the identification with the work field, being indissolubly linked to a professional practice, continued learning as well as professional development and representation, configured under functional (knowledge and professional profile), contextual (organizational and institutional guidelines) and identity (to do and to be in the profession) scopes. Over the past few years, researches have investigated the relationship between identity formation and early training, especially regarding practices which bring individuals closer to their future intervention locus, such as in the case of curricular internship. However, such studies are frequent in the context of licentiate degree, leaving only a few papers directed to the formation of Physical Education bachelor?s degree. Therefore, the aim of this dissertation was to analyze how the Curricular Internship of Physical Education Bachelor?s Degree from Higher Education Institutions of Maringá, benefits/influences the formation of students and interns? professional identity. Our investigation involved students from the last year of Physical Education Bachelor?s Degree courses, whose participation occurred through a questionnaire specifically built and validated for our study as well as focus group. For data analysis, we applied descriptive and inferential statistics by using Statistical Package for Social Sciences (SPSS) 20.0 software, qualitative analysis through record content analysis by using Qualitative Solutions Research Nvivo10 software, in addition to documental analysis of the Professional Internship Guidelines, measures, teaching planning, and student?s profile from the courses investigated. The results indicate that the bachelor?s formation in Physical Education is strongly linked to assumptions of health promotion and rehabilitation as well as to the acquisition of physical and sport skills, requiring a view of the scopes of collective health and actions which break with instrumental, diagnostic and prescriptive issues. Regarding the curricular internship and professional representation, we verified that the internship has increasingly benefited the constitution of the functional scope compared to the contextual and identity scopes, making emerge the necessity of actions to provide the intern with better autonomy, maximizing the retrieval of prior knowledge and sharing of experiences with teachers, reducing the value charged to bureaucratic matters. It has been proved the necessity to restructure the actions of the curricular internship, especially regarding the contextual and identity scopes in order to rethink strategies of monitoring, orientation and professional socializations. In this context, we conclude that to contribute effectively to for the professional identity of Physical Education bachelor?s degree student, the curricular internship requires a new pedagogical approach on the actions which support professional autonomy, their relationships with what to be in the professional practice and the feeling of social belonging, bringing what is learned closer to what is demanded in the daily practice of this occupation